Evaluación de impacto proyecto Salud sexual y reproductiva de adolescentes en Medellín. “Sol y Luna” Componente cualitativo, 2008 (2009)
ABSTRACT: Article that shows the impact results of the project “Sol y Luna” on its qualitative component; the objective of this project is to prevent early pregnancy, prejudicial behavior on the sexual and reproductive life of the teenage population, specifically in the communes 1 thru 4 in the city of Medellin, which report the highest numbers of this issues in the city. This project is financially supported by the Interamerican Development Bank (IDB). Study Objective: to evaluate the impact of the strategies of the “Sol y Luna” project of the mayor’s office on Medellin, its beneficiaries starting from qualitative social investigation techniques. Method: descriptive ethnographic study with qualitative social investigation techniques (focused discussion groups (FGD), interviews and documental analysis). Results: the interviewed consider the project appropriate in its methodology and opportune implementation; the development of the nurses in the health centers and outside them, was the base for the recognition of the health center as a space for the community, they supported the construction of a renewed confidence in the health personal and birth control; it is recognized that the project only reached the level of acquisition of information, but not to the change of attitude and abilities of the teenagers involved. The documental research emphasizes in the need to insist on the same micro social aspects involved with the teenage pregnancy. Conclusions: the project achieved progresses in the topic of teenage birth control, specifically in the demythologization of the birth control methods, confidence and reconfiguration of the negative perspective in relation to the health services; no changes were shown in the attitude of the population that risks their sexual and reproductive health or the acquisition of abilities that support the achievement of the sexual and reproductive health. The analysis carried out through the documental checking shows that it is necessary to analyze and get involved in the macro structural aspects of the society – social inequality, poverty, precarious employment, communication medias, violence and armed conflict- if not influenced this determiners it will be difficult the transformation of this phenomena in the city.